(untitled) (Third Sector Social Economic Review, 2026)
Sustainable tourism is a form of development that prioritizes the protection of the environment and the preservation of cultural heritage and traditional values of local communities. It seeks to promote destinations’ progress in economic, social, and environmental terms. The World Tourism Organization has identified 140 indicators, spanning economic, social, and environmental aspects, to gauge sustainable tourism practices. This study aims to analyze and evaluate the provinces in the Aegean Region concerning these sustainable tourism indicators. Sustainable tourism plays a pivotal role in ensuring the longevity of tourism activities. When sustainable planning is not adopted, the quality of a tourism area will decrease and thus its preference by tourists will decrease. For this reason, the desired benefit from tourism will not be obtained. By examining sustainable tourism indicators, the goal is to assess the current situation in the Aegean Region, identify areas needing improvement, and facilitate efforts toward enhancement. Within the scope of environmental indicators, solid waste collection, air pollutant sulfur dioxide (SO2) and particulate matter (PM10) values, use of natural resources (organic agriculture production), ecosystem sensitivity, erosion control studies and afforestation areas were determined in the Aegean Region. With the determination of these indicators, the negative effects on the environment will be revealed and the measures to be taken for the realization of environmental sustainability will be determined. Tourism and the environment are in close relationship with each other. Investigating the effects of tourism on the environment is important for achieving success in sustainable tourism.